Outcomes of psychiatric interviews and self-rated symptom scales in people on sick leave for common mental disorders: an observational study. Issue 6 (22nd June 2022) - af Winklerfelt Hammarberg, Sandra; Westman, Jeanette; Hange, Dominique; Finnes, Anna; Björkelund, Cecilia; Hällgren, Jonas; Skoglund, Ingmarie; Nager, Anna
Abstract : Objectives: To investigate the correspondence between diagnoses on sick leave certificates and diagnoses made in structured psychiatric interviews. Secondary aims were to investigate length of sick leave by diagnoses on sick leave certificates, diagnoses made in structured interviews and symptom severity. Design: Observational study consisting of a secondary analysis of data from a randomised controlled trial and an observational study. Setting: The regions of Stockholm and Västra Götaland, Sweden. Participants: 480 people on sick leave for common mental disorders. Interventions: Participants were examined with structured psychiatric interviews and self-rated symptom severity scales. Outcome measures: (1) Sick leave certificate diagnoses, (2) diagnoses from the Mini International Neuropsychiatric Interview and the Self-rated Stress-Induced Exhaustion Disorder (SED) Instrument (s-ED), (3) symptom severity (Montgomery-Asberg Depression Rating Scale-self-rating version and the Karolinska Exhaustion Disorder Scale) and (4) number of sick leave days. Results: There was little correspondence between diagnoses on sick leave certificates and diagnoses made in structured psychiatric interviews. Many participants on sick leave for SED, anxiety disorder or depression fulfilled criteria for other mental disorders. Most on sick leave for SED (76%) and anxiety disorder (67%) had depression (p=0.041). Length of sick leave did not differ by certificate diagnoses. Participants with SED (s-ED) had longer sick leave than participants without SED (144 vs 84 days; 1.72 (1.37–2.16); p<0.001). More severe symptoms were associated with longer sick leave. Conclusion: Diagnoses on sick leave certificates did not reflect the complex and overlapping nature of the diagnoses found in the structured psychiatric interviews. This finding is relevant to the interpretation of information from health data registers, including studies and guidelines based on these data. A result of clinical interest was that more severe symptoms predicted long-term sick leave better than actual diagnoses.